Measurement of the inelastic pp cross-section at a centre-of-mass energy of √s = 7 TeV - Aaij, Roel; Adeva, B.; Adinolfi, M.; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; et al. (Journal of high energy physics, 2015)
The cross-section for inelastic proton-proton collisions, with at least one prompt long-lived charged particle of transverse momentum pT> 0.2GeV/c in the pseudorapidity range 2.0 < η < 4.5, is measured by the LHCb experiment at a centre-of-mass energy of √s = 7 TeV. The cross-section in this kinematic range is determined to be σinelacc= 55.0 ± 2.4 mb with an experimental uncertainty that is dominated by systematic contributions. Extrapolation to the full phase space, using Pythia 6, yields σinel = 66.9 ± 2.9 ± 4.4 mb, where the first uncertainty is experimental and the second is due to the extrapolation.
The LHCb Collaboration: R. Aaij, B. Adeva, M. Adinolfi, O. Aquines Gutierrez, S. Bachmann, A. Bien, J. Blouw, M. Britsch, A. Comerma-Montells, M. De Cian, F. Dordei, S. Esen, C. Färber, M. Fontana, E. Gersabeck, L. Grillo, X. Han, S. Hansmann-Menzemer, A. Jaeger, M. Kolpin, K. Kreplin, G. Krocker, B. Leverington, J. Marks, M. Meissner, M. Neuner, T. Nikodem, M. Schmelling, P. Seyfert, M. Stahl, S. Stahl, U. Uwer, M. Vesterinen, R. Waldi, S. Wandernoth, D. Wiedner, A. Zhelezov [und 663 weitere]
Gesehen am 07.10.2020